SEEKING A QUOTE ON NYSE - A CHINESE CASE STUDY - Pan, Qimin (2007)
The last two decades have seen an active market for initial public offerings (IPOs) of equity securities in the U.S. and around the world. This market activity has been accompanied by a growing empirical and theoretical literature documenting and explaining the patterns (Welch and Ritter, 2002). With the rapid development of China's economy, since the policy of reforming and opening-up was executed 27 years ago, China has become more involved in the global economy system(Zhang, 2002). More and more Chinese companies started to enter the international stock markets for capital raising. Going public in the international stock exchanges is a good way for Chinese companies to get investments and capital to expand their business. Today, over 100 Chinese companies have been listed on Hong Kong Stock Exchange, New York Stock Exchange, Nasdaq etc. There are many options for Chinese companies to issue shares. But, in this thesis, only listing on the New York Stock Exchange is to be discussed, mainly because New York Stock Exchange can be taken as the representative of world stock markets, and going to do some research related to China and U.S purposely. This thesis provides the basic knowledge of New York Stock Exchange, and describes the general matters related to listing on New York Stock Exchange including listing requirements and procedures. Furthermore, it conducts an analysis of the possibility and feasibility of Chinese company's listing in U.S, with a recently listed Chinese company E-House China Holding Limited as an illustration. Its objective is to help Chinese companies get a better understanding of New York Stock Exchange. Moreover, IPO valuation mechanism and IPO pricing is also discussed in the thesis. The thesis is expected to be valuable for Chinese companies seeking overseas listing, and anyone who has interest in this subject.